PROGRAM ACARA GEGIRANG SEBAGAI MEDIA KOMUNIKASI BERLANDASKAN AGAMA HINDU DI LEMBAGA PENYIARAN PUBLIK (LPP) TVRI STASIUN BALI: GEGIRANG - Ida Bagus Made Tastra; Ida Ayu Tary Puspa; I Gede Januariawan (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2022)
The Public Broadcasting Institute (LPP) TVRI Bali Station is one of the local television stations that is close to the culture of the local community. In addition to emphasizing local cultural aspects, this television station also has the privilege of highlighting the lives of religious communities, especially Hindus in Bali. The focus of this research is to examine the communication patterns that are applied to the Gegirang program as a Hindu Religion-based Communication Media at the Bali Station TVRI Public Broadcasting Institution (LPP). The function of the Gegirang program as a Communication Media based on Hinduism at the Bali Station TVRI Public Broadcasting Institution (LPP). Implications of the Gegirang program as a Communication Media based on Hinduism at the Bali Station TVRI Public Broadcasting Institution (LPP). This study uses a qualitative approach using the case study method. The results of this study indicate that the communication pattern applied to the Gegirang program as a Hindu Religionbased Communication Media at the Bali Station TVRI Public Broadcasting Institution (LPP) has a circular linear pattern. The function of the Gegirang program as a Communication Media based on Hinduism at the Bali Station TVRI Public Broadcasting Institution (LPP) is to preserve Balinese culture based on Hinduism. The implications of the Gegirang program as a Hindu Religion-based Communication Media at the Bali Station TVRI Public Broadcasting Institution (LPP) for the audience have an impact on cognitive strengthening, affective formation, and behavioral development.